2018
DOI: 10.1007/s00586-018-5640-y
|View full text |Cite
|
Sign up to set email alerts
|

Proximal junctional kyphosis in thoracic adolescent idiopathic scoliosis: risk factors and compensatory mechanisms in a multicenter national cohort

Abstract: PJK is a frequent complication in thoracic AIS, occurring 16%, but remains often asymptomatic (less than 3% of revisions in the entire cohort). An interesting finding is that patients with high pelvic incidence and consequently large LL and TK were more at risk of PJK. As demonstrated in ASD, one of the causes of PJK might be postoperative posterior imbalance that can be due to increased LL, insufficient TK or inflection point shift during surgery. These slides can be retrieved under Electronic Supplementary M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 17 publications
4
58
0
Order By: Relevance
“…Although Wang et al reported greater Scoliosis curve correction to be associated with PJK, 49 we and others did not observe this. 54 Patients with PJK had smaller PI and larger PI–LL mismatch after surgery compared to the noPJK group. Yang et al suggested that a smaller PI implied poor capacity for pelvic compensation to sagittal imbalance and proposed that a critical PI for compensation was greater than 39°, 41 which is close to the pre- and post-operative PI seen in PJK patients within our cohort, 37.8° and 39.8°, respectively.…”
Section: Discussionmentioning
confidence: 88%
“…Although Wang et al reported greater Scoliosis curve correction to be associated with PJK, 49 we and others did not observe this. 54 Patients with PJK had smaller PI and larger PI–LL mismatch after surgery compared to the noPJK group. Yang et al suggested that a smaller PI implied poor capacity for pelvic compensation to sagittal imbalance and proposed that a critical PI for compensation was greater than 39°, 41 which is close to the pre- and post-operative PI seen in PJK patients within our cohort, 37.8° and 39.8°, respectively.…”
Section: Discussionmentioning
confidence: 88%
“…This was lower than previously reported incidence at 7% to 46%. 3,4,6,[8][9][10]12 This discrepancy may be due to the difference of PJA/PJK definition, which varied among studies. Some studies measure the difference between pre-and postoperative radiographs, while others, similar to this study, measure the difference between the immediate postoperative and latest follow-up film.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in our study, one-hook/one-screw at UIV had no PJK with average 2.2 years follow-up. Ferrero et al 12 analyzed the incidence of PJK in AIS and reported one-hook/one-screw was equivalent to bilateral hooks at UIV in terms of PJK 12 . We speculate that one-hook/one-screw constructs reduced the rate of PJK by allowing us to keep at least one facet capsule away from violation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23][24] Furthermore, inadequate restoration of TK at the instrumented segments may lead to a compensatory increase in TK at the noninstrumented upper junction, thus increasing the chance of PJK in such patients. 25,26 Based on our analysis of the asymptomatic volunteers, the ideal relationship between thoracic and lumbar curves was established as TK to be 41% of LL, with a deviation from this relationship indicating either inadequate or excessive kyphotic restoration. Our study showed that patients who had a lack of kyphosis restoration in relation to lordosis correction (defined as DTK < 41% DLL) exhibited a higher rate of PJK in comparison to those who achieved kyphosis restoration in excess (DTK > 41%).…”
Section: Discussionmentioning
confidence: 99%